Avaliação do feijão (Phaseolus vulgaris L.) partido como ingrediente em alimentos extrusados para gatos - Ponciano Neto, Bruna (2015)
The aim was to evaluate the inclusion of broken bean (BB) in extruded foods for cats. To achieve this, five extruded diets containing approximately 6% moisture, 30% crude protein, 16% fat, 2.8% crude fiber and 7% mineral matter, including increasing levels (0.0%, 7.5%, 15.0%, 22.5% and 30.0%) of the tested ingredient were produced. To evaluate the nutritional value of FP the substitution method was performed, in which the FP replaced in 30.0% the control (0.0% of FP) diet. During the extrusion process concentrations of trypsin inhibitors (IT) and haemagglutinin (HEM) were measured and at the end of process the quality of the extrudate was analyzed. The Control diet and 15.0% FP diet had their palatability assessed. For the digestibility trial, urinary pH and determination of fermentation activity, 30 adult cats were used (5.03 ± 0.27 kg) allotted to five treatments. The extrusion process was effective in inactivating IT and HEM. Increased inclusion of BB decreased linearly (P<0.05) the rate of radial expansion and specific length of the kibbles, consequently increased linearly (P<0.05) the specific density and shear force. The inclusion of FP influenced negatively the palatability of the diet, however the 15.0% inclusion was not rejected. The metabolizable energy, ADC of CP, starch and FDT of the PF were respectively 3101.46 kcal/kg, 71.38%, 95.58% and 54.84%. Urine pH increased significantly (P<0.05) from the 15.0% inclusion. No significant differences (P>0.05) for feed intake, digestibility of nutrients and energy, quality and fermentation parameters of the feces, or protein quality were observed, indicating that the FP is a satisfactory source of protein and energy for cats, and an important alternative ingredient.